Impact of the COVID-19 pandemic on symptoms of anxiety and depression and health-related quality of life in older patients with chronic kidney disease - C. G. N. Voorend (BMC, 2021)
Abstract Background Older patients with advanced chronic kidney disease are at increased risk for a severe course of the coronavirus disease-2019 (COVID-19) and vulnerable to mental health problems. We aimed to investigate prevalence and associated patient (demographic and clinical) characteristics of mental wellbeing (health-related quality of life [HRQoL] and symptoms of depression and anxiety) before and during the COVID-19 pandemic in older patients with advanced chronic kidney disease. Methods An ongoing Dutch multicentre prospective cohort study enrols patients of ≥70 years with an eGFR < 20 mL/min/1.73m2 from October 2018 onward. With additional questionnaires during the pandemic (May–June 2020), disease-related concerns about COVID-19 and general anxiety symptoms were assessed cross-sectionally, and depressive symptoms, HRQoL, and emotional symptoms longitudinally. Results The 82 included patients had a median age of 77.5 years (interquartile range 73.9–82.1), 77% were male and none had tested positive for COVID-19. Cross-sectionally, 67% of the patients reported to be more anxious about COVID-19 because of their kidney disease, and 43% of the patients stated that their quality of life was reduced due to the COVID-19 pandemic. Compared to pre-COVID-19, the presence of depressive symptoms had increased (11 to 22%; p = .022) and physical HRQoL declined (M = 40.4, SD = 10.1 to M = 36.1, SD = 10.4; p < .001), particularly in males. Mental HRQoL (M = 50.3, SD = 9.6 to M = 50.4, SD = 9.9; p = .913) and emotional symptoms remained similar. Conclusions Older patients with advanced chronic kidney disease suffered from disease-related anxiety about COVID-19, increased depressive symptoms and reduced physical HRQoL during the COVID-19 pandemic. The impact of the pandemic on this vulnerable patient group extends beyond increased mortality risk, and awareness of mental wellbeing is important. Trial registration The study is registered at the Netherlands Trial Register (NTR), trial number NL7104. Date of registration: 06-06-2018.